2021
DOI: 10.1126/sciadv.abd9138
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical energy conversion with selectively decayed wood

Abstract: Producing electricity from renewable sources and reducing its consumption by buildings are necessary to meet energy and climate change challenges. Wood is an excellent “green” building material and, owing to its piezoelectric behavior, could enable direct conversion of mechanical energy into electricity. Although this phenomenon has been discovered decades ago, its exploitation as an energy source has been impaired by the ultralow piezoelectric output of native wood. Here, we demonstrate that, by enhancing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 49 publications
3
43
0
Order By: Relevance
“…Recently Sun et al (2020Sun et al ( , 2021 reported about a simple and effective way to strongly enhance the electrical output from electromechanical coupling in wood by means of delignification (Figure 3). Balsa wood was found to be especially suitable, most probably thanks to very low cell wall thicknesses.…”
Section: Wood As Sensor and Energyharvesting Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Sun et al (2020Sun et al ( , 2021 reported about a simple and effective way to strongly enhance the electrical output from electromechanical coupling in wood by means of delignification (Figure 3). Balsa wood was found to be especially suitable, most probably thanks to very low cell wall thicknesses.…”
Section: Wood As Sensor and Energyharvesting Materialsmentioning
confidence: 99%
“…Balsa wood was found to be especially suitable, most probably thanks to very low cell wall thicknesses. Removal of lignin could be achieved both by chemical (treatment with concentrated acetic acid and hydrogen peroxide mixtures at 80 °C) (Sun et al 2020) and biological treatments (white rot fungi) (Sun et al 2021). The resulting "wood sponge" displayed a spring-like microstructure due to cell wall breakage, leading to enhanced compressibility.…”
Section: Wood As Sensor and Energyharvesting Materialsmentioning
confidence: 99%
“…[ 11–14 ] Nanocellulose‐derived functional materials integrate important cellulosic properties with the features of nanomaterials, which are now being extensively applied in diverse fields such as paper, packaging, optoelectronics, wearable technologies, soft robotics, energy storage, antibacterial coatings, tissue scaffolds, drug delivery, and beyond. [ 15–31 ]…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Nanocellulose-derived functional materials integrate important cellulosic properties with the features of nanomaterials, which are now being extensively applied in diverse fields such as paper, packaging, optoelectronics, wearable technologies, soft robotics, energy storage, antibacterial coatings, tissue scaffolds, drug delivery, and beyond. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] In general, nanocellulose can be classified into three types, that is, cellulose nanocrystals (CNCs), cellulose nanofibrils (CNFs), and bacterial cellulose (BC), according to their synthesis strategies, primarily the cellulosic source and processing conditions. [32][33][34] CNCs can be isolated from several sources, such as algae, plants, and wood, by chemical hydrolysis or oxidation; conversely, CNFs are mechanically produced by delaminating plant-based cellulose (Figure 1a).…”
mentioning
confidence: 99%
“…6 Enabling wood with new functionalities, including visual environmental responsiveness 7 is an important factor to promote its widespread use in buildings beyond conventional structural applications. 6,[8][9][10][11][12] Luminescent wood has recently caught considerable attention as an attractive substitute for more conventional materials for indoor and outdoor lighting applications, such as brittle glass and non-biodegradable plastics, thanks to woods sustainability and promising anisotropic optical properties. 7,[13][14][15][16][17] However, state-of-art wood-based lighting appliances require lengthy procedures for their preparation, including delignification and impregnation with often non-biodegradable polymers to improve the matrix transparency, and the use of potentially toxic fluorophores.…”
Section: Introductionmentioning
confidence: 99%